2013
DOI: 10.1308/003588413x13511609956336
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic surgical management of colorectal lung metastases: a questionnaire survey of members of the Society for Cardiothoracic Surgery in great Britain and Ireland

Abstract: IntroductionDistant metastases to liver and lung are not uncommon in colorectal cancer. Resection of metastases is accepted widely as the standard of care. However, there is no firm evidence base for this. This questionnaire survey was carried out to assess the current practice preferences of cardiothoracic surgeons in Great Britain and Ireland.MethodsAn online questionnaire survey was emailed to cardiothoracic surgeons in Great Britain and Ireland. The survey was live for 12 weeks. Responses were collated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Currently, FDG-PET is used as a complementary examination to determine the metabolic activity of suspect lung nodules, define lymph nodal involvement, and detect extrathoracic recurrence. However, its use in the preoperative setting for CRC patient evaluation is an increasing trend in the thoracic surgery community [6,13]. Conversely, the precision of FDG-PET in the evaluation of CRC pulmonary metastases is a rarely investigated topic [20].…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, FDG-PET is used as a complementary examination to determine the metabolic activity of suspect lung nodules, define lymph nodal involvement, and detect extrathoracic recurrence. However, its use in the preoperative setting for CRC patient evaluation is an increasing trend in the thoracic surgery community [6,13]. Conversely, the precision of FDG-PET in the evaluation of CRC pulmonary metastases is a rarely investigated topic [20].…”
Section: Commentmentioning
confidence: 99%
“…Although still a subject of debate, lung metastasectomy by open thoracotomy is widely accepted by most surgical teams with, for selected populations, reported 5-year overall survival rates of 41% to 68% after radical resection [2,3]. Nevertheless, among alternative metastasisdirected local treatments, minimally invasive surgery (video-assisted thoracic surgery), stereotactic body radiotherapy, and radiofrequency ablation, with or without systemic chemotherapy [4,5], are commonly proposed to CRC metastatic patients in routine clinical practice [6]. Furthermore, a copious amount of literature has indicated that, in CRC patients undergoing lung metastasectomy or local treatment, certain factors, including lymph node involvement (LNI) and number of pulmonary metastases, are consistent predictors of the outcome [3,[7][8][9][10][11].…”
mentioning
confidence: 99%
“…In a recent survey published by the ESTS in 2008, the preferred surgical approach in case of unilateral and bilateral pulmonary lesions was VATS in 28.8% and 20% respectively [29]. More recently, current practice preferences of cardiothoracic surgeons in Great Britain and Ireland have been investigated by an online questionnaire survey reporting that Video assisted thoracoscopic surgery (VATS) was used by 85% of surgeons in case of isolated pulmonary metastatic lesions [30]. Although these data are important to reflect the opinion and practice of thoracic surgeons, there is no hard data on the percentage of procedures performed by VATS in the field of pulmonary metastasectomy.…”
Section: Controversiesmentioning
confidence: 99%
“…Britain and Ireland) revealed evidence of considerable variation in practice. 77 Specifically, although a solitary lung metastasis was the most frequent indication for surgery, 59 (88%) of respondents did not consider lung lesions in the presence of liver metastases as contra-indications to surgery. To address this, PulMiCC a randomised trial of pulmonary metastasectomy in colorectal cancer is undertaking a feasibility study in 11 centres in the United Kingdom with a view to the conduct of a randomised trial.…”
Section: Management Of Colorectal Cancer With Liver and Lung-limited mentioning
confidence: 98%